Total Quality Management dalam Meningkatkan Kualitas Lembaga Amil Zakat - Dina Qurotun Nisa; Aep Kusnawan; Herman Herman (Jurusan Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2019)
The purpose of this study is to find out (1) customer focus, (2) process improvement, (3)Total involvement in improving the quality of the Exact Zakat Center (PZU). The method used is descriptive method with the type of field research. Data collection is done by interview, observation and documentation. With the results of the research found, namely: (1). PZU Persis understands the position, rights and obligations of the customer as a focus on customers in improving the quality of the institution (2). PZU Exactly in terms of process improvement, has carried out a number of activities and breakthroughs oriented to the improvement of an institution (3). Total involvement, PZU Persis always involves all elements in the institution in all activities and policy making related to the institution and believes that integrated quality control will not succeed only with the strong will of the leadership, but must also be supported by the participation of employees, and vice versa . This study also indicates that in its theoretical implications, TQM can be applied to non-profit institutions.